TINJAUAN YURIDIS NON-FUNGIBLE TOKEN (NFT) SEBAGAI OBJEK JAMINAN KEBENDAAN FIDUSIA DI INDONESIA - NIM. A1011211156, WULANDARI SEPTIANI KUSUMA DEWI (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract This research aims to analyze the legal use of Non-Fungible Tokens (NFT) as an object of fiduciary guarantee in Indonesia. Along with technological developments at this time Blockchain technology presents innovations in the form of digital assets called Non-Fungible Tokens (NFT), which have unique characteristics. Non-Fungible Token (NFT) as an object of fiduciary guarantee can be associated with Law Number 28 of 2014 concerning Copyright and other laws and regulations. The purpose of this study is to determine and analyze whether Non-Fungible Tokens (NFT) can be used as an object of fiduciary guarantee in Indonesia by analyzing the legal basis that applies in the implementation of Non-Fungible Tokens (NFT) as an object of fiduciary guarantee. The research method used is a normative judicial research method which is descriptive in nature with a statutory and conceptual approach. This research is analyzed based on Indonesian laws and regulations and data sources come from literature study materials. The results of this study show that NFTs can be categorized as